Land subdivision: How students determine equal area - Aan Hendroanto (Universitas Ahmad Dahlan, 2020)
This study aims to support student’s understanding of the properties of a bisector related to the area of the triangle. A context and a set of activities is design based on Realistic Mathematics Education (RME) theory to develop students’ understanding and to engage them in meaningful activities. Design research is chosen as the research approach with two cycles of experiment. A context of land subdivision problem was selected to activate students’ prior knowledge and to bring them into the activities. At First, the activities is presented in small group of mathematics students and in the regional mathematics competition as one of the final question for the finalists. Then, the second cycle is conducted in the classroom with students from mathematics education program in Universitas Ahmad Dahlan. The result showed that none of the students and finalists in the competition were able to solve the question because they do not have idea how to do land subdivision. They cannot use their prior knowledge of bisector to solve the problem. After revising the activities, in the classroom, all groups in the class were able to solve the problem. These activities are land subdivision with three different levels of difficulties and purposes.